Role of DNA methylation in expression and transmission of porcine endogenous retroviruses - Matousková, Magda; Vesely, Pavel; Daniel, Petr; Mattiuzzo, Giada; Hector, Ralph D; Scobie, Linda; Takeuchi, Yasuhiro; Hejnar, Jirí (Journal of virology, 2013)
Porcine endogenous retroviruses (PERV) represent a major safety concern in pig-to-human xenotransplantation. To date, no PERV infection of a xenograft recipient has been recorded; however, PERVs are transmissible to human cells in vitro. Some recombinants of the A and C PERV subgroups are particularly efficient in infection and replication in human cells. Transcription of PERVs has been described in most pig cells, but their sequence and insertion polymorphism in the pig genome impede identification of transcriptionally active or silenced proviral copies. Furthermore, little is known about the epigenetic regulation of PERV transcription. Here, we report on the transcriptional suppression of PERV by DNA methylation in vitro and describe heavy methylation in the majority of PERV 5' long terminal repeats (LTR) in porcine tissues. In contrast, we have detected sparsely methylated or nonmethylated proviruses in the porcine PK15 cells, which express human cell-tropic PERVs. We also demonstrate the resistance of PERV DNA methylation to inhibitors of methylation and deacetylation. Finally, we show that the high permissiveness of various human cell lines to PERV infection coincides with the inability to efficiently silence the PERV proviruses by 5'LTR methylation. In conclusion, we suggest that DNA methylation is involved in PERV regulation, and that only a minor fraction of proviruses are responsible for the PERV RNA expression and porcine cell infectivity.
Keywords: Endogenous Retroviruses; koncové repetice; Animals; Kidney; Swine, Miniature; Proviruses; DNA, Viral; lidé; replikace viru; miniaturní prasata; Terminal Repeat Sequences; prasata; Swine Diseases; messenger RNA; proviry; polymerázová řetězová reakce s reverzní transkripcí; kultivované buňky; metylace DNA; RNA, Messenger; epigeneze genetická; Cells, Cultured; endogenní retroviry; Reverse Transcriptase Polymerase Chain Reaction; nemoci prasat; Swine; DNA Methylation; zvířata; Virus Replication; ledviny; kvantitativní polymerázová řetězová reakce; Epigenesis, Genetic; DNA virů; Real-Time Polymerase Chain Reaction; Humans